Physical activity and the coronavirus pandemic: an urgent time to change the recommendation focus - Luiz Guilherme Grossi Porto; Guilherme E. Molina; Victor K. Matsudo (Revista Brasileira de Atividade Física e Saúde)
The COVID-19 pandemic is disrupting the routine daily life of millions of people. The pandemic associated restrictive measures impose unprecedented challenges, including the need to stay physically active in a social distancing scenario that drastically reduces access to physical activity (PA) spaces and opportunities. Therefore, we aimed to discuss the need for an urgent change in the main focus of PA recommendations. The total of PA needed for health promotion has been focused on the minimum of 150min/moderate-to-vigorous PA/week. It is time for a call for action toward shifting the focus of PA recommendations. Instead of the traditional “doing at least 150min/week of PA, and less than that if you can’t reach that goal”, recommendations should emphasize the idea of “move more, sit less and, if possible, accumulate 150min/PA/week. The coronavirus pandemic, its associated social distancing and impacts on PA opportunities, impose an urgent change in PA recommendation main focus.